2019
DOI: 10.1111/ahg.12360
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine phenotype features of fetuses with Williams–Beuren syndrome and literature review

Abstract: Williams-Beuren syndrome (WBS) is a well-defined multisystem chromosomal disorder that is caused by a chromosome 7q11.23 region heterozygous deletion. We explored prenatal diagnosis of WBS by ultrasound as well as multiple genetic methods to characterize the structural variants of WBS prenatally. Expanded noninvasive prenatal testing (NIPT-plus) was elected as a regular prenatal advanced screen for risk assessments of fetal chromosomal aneuploidy and genome-wide microdeletion/microduplication syndromes at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 45 publications
2
22
3
Order By: Relevance
“…As previously described, congenital cardiovascular defects are the most clinically significant in 80% of patients with Williams-Beuren syndrome, which is caused by haplo insufficiency in the elastin (ELN) [ 23 , 24 ]. The ultrasound feature of case 10 was CoA and FGR, which was also reported in a study by Yuan et al [ 25 ]. In their study, the researchers found that the most common ultrasound manifestations of William-Beuren syndrome in prenatal cases were FGR and congenital cardiovascular abnormalities mainly involving supravalvular aortic stenosis, VSD, or aortic coarctation.…”
Section: Discussionsupporting
confidence: 80%
“…As previously described, congenital cardiovascular defects are the most clinically significant in 80% of patients with Williams-Beuren syndrome, which is caused by haplo insufficiency in the elastin (ELN) [ 23 , 24 ]. The ultrasound feature of case 10 was CoA and FGR, which was also reported in a study by Yuan et al [ 25 ]. In their study, the researchers found that the most common ultrasound manifestations of William-Beuren syndrome in prenatal cases were FGR and congenital cardiovascular abnormalities mainly involving supravalvular aortic stenosis, VSD, or aortic coarctation.…”
Section: Discussionsupporting
confidence: 80%
“…In previous literature reports, the most common ultrasound features were: IUGR (82.35%), SVAS (40%), VSD (30%), AC (20%), and PAS (20%) [ 10 ]. However, in our study, the incidence of IUGR (25%) and SVAS (12.5%) were lower than in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Trisomy 13, 17 and 18 [11][12][13] Cri-du-chat syndrome (5p15.2 or 5p15.3 deletion) [14][15][16] Williams-Beuren syndrome (7q11.23 deletion) [17] Monogenic syndromes Cornelia de Lange syndrome (NIPBL mutation) [10,[25][26][27] Smith-Lemli-Opitz syndrome (DHCR7 mutation)…”
Section: Fetal Chromosomal Aberrationsmentioning
confidence: 99%
“…Similarly, FGR is the most common symptom of trisomy 17; however, the presence of this aberration is very rare [ 13 ]. The other genetic disorders with the same prenatal manifestation as FGR are Cri-du-chat syndrome (CdCS), resulting from a deletion of the short ( p ) arm of chromosome 5 [ 14 , 15 , 16 ], and Williams–Beuren syndrome, caused by a heterozygous deletion in the chromosome 7q11.23 region [ 17 ].…”
Section: Fetal Fgr Causesmentioning
confidence: 99%